Implementasi Teknologi Asynchronous dengan Menggunakan Squid Untuk Menyimpan Cache Website - Ade Subarqah; Tengku M. Diansyah; Divi Handoko (Universitas Harapan Medan, 2021)
Information technology, especially the internet, is currently growing very rapidly, due to the increasing number of people who disseminate information through the internet. The development of the number of users of Internet information technology is currently not followed by the addition of appropriate bandwidth, so problems often arise related to the speed of access to get internet services. An easy way to save bandwidth and force authentication on information traffic is to use squid. The use of Squid can be used to increase the need to speed up information retrieval. By using the Squid application, the router can be used as a proxy server for internet web cache. At the time of installing Squid without a proxy, testing was carried out on the https://www.kompas.com url and the results of the first load on a website resulted in a load time of 36 seconds, there was no difference in bandwidth usage and time whether using a proxy server or not, but the second page load on the same site with a faster load time of 30 seconds will save bandwidth. Then the installation of Squid using a proxy was carried out, testing was carried out on the https://www.kompas.com url and the results of the first load on a website resulted in a load time of 34 seconds, there was no difference in bandwidth usage and time, whether using a proxy server or not, but on the second page load on the same site with a faster load time of 16 seconds, it will save bandwidth and be faster by using squid compared to not using squid.